2021
DOI: 10.1037/pspi0000311
|View full text |Cite
|
Sign up to set email alerts
|

Friendship jealousy: One tool for maintaining friendships in the face of third-party threats?

Abstract: Friendships can foster happiness, health, and reproductive fitness. But friendships end-even when we might not want them to. A primary reason for this is interference from third parties. Yet little work has explored how people meet the challenge of maintaining friendships in the face of real or perceived threats from third parties, as when our friends inevitably make new friends or form new romantic relationships. In contrast to earlier conceptualizations from developmental research, which viewed friendship je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 170 publications
(324 reference statements)
0
45
0
Order By: Relevance
“…While this may seem like a simplistic prediction, there is a prevalent belief that women are unconcerned with same-sex competition (Beckmann & Menkhoff, 2008;Hennighausen et al, 2016;Puts, 2010Puts, , 2016, unless the competition is matingrelated (Arnocky & Piche, 2014;Davis et al, 2018;Fink et al, 2014;Klavina & Buunk, 2013). This misperception runs counter to research showing that women's competition occurs across the life course (Low, 2017) and in a variety of social relationships (Ayers et al, 2020;Krems et al, 2021;Nagamuthu & Page-Gould, 2017).…”
mentioning
confidence: 97%
“…While this may seem like a simplistic prediction, there is a prevalent belief that women are unconcerned with same-sex competition (Beckmann & Menkhoff, 2008;Hennighausen et al, 2016;Puts, 2010Puts, , 2016, unless the competition is matingrelated (Arnocky & Piche, 2014;Davis et al, 2018;Fink et al, 2014;Klavina & Buunk, 2013). This misperception runs counter to research showing that women's competition occurs across the life course (Low, 2017) and in a variety of social relationships (Ayers et al, 2020;Krems et al, 2021;Nagamuthu & Page-Gould, 2017).…”
mentioning
confidence: 97%
“…Recent research on how feelings of friendship jealousy might be a tool to prevent the defection of friends is an initial foray into just one area of ally retention. Krems et al (2021) found that feelings of friendship jealousy spur individuals to act in ways that might prevent the loss of valued friends; for example, friendship jealousy can cause individuals to increase the physical distance between their best friends and potential "friend poachers." Other work remains to be conducted, to show the ways in which people engage in the maintenance of various affiliative bonds, including affinal bonds (with in-laws), neighborhood bonds, and so on.…”
Section: Future Directionsmentioning
confidence: 99%
“…It is regularly used by social and personality psychologists to understand the causal mechanisms of a treatment effect across a broad span of topics. For example, recent publications in the Journal of Personality and Social Psychology use mediation analysis to understand: how experience of awe (treatment) affects life satisfaction (outcome) via appraisal of vastness in relation to the self, and changes in daily stress levels (Bai et al, 2021); how either support-or oppose-framed attitudes (treatment) affects sharing (outcome) via value expressiveness and impression management (Catapano & Tormala, 2021); how perceived target's extraversion (treatment) affects target's reputation of having leadership potential (outcome) via target's reputation of extraversion (Costello & Srivastava, 2021); how helping opportunities (treatment) affect moral outrage (outcome) via perceived reputation benefits of punishment, and general reputation concerns (Jordan & Rand, 2020); how friendship jealousy (treatment) affects intent to engage in friend guarding via jealousy, neutrality, happiness, sadness, and anger (Krems et al, 2021); and how search for meaning in life (non-randomized treatment) affects support for political violence (outcome) via sensation seeking and willingness to self-sacrifice (Schumpe et al, 2020).…”
Section: Recommendations For Improving Causal Inference Of Mediation Analysismentioning
confidence: 99%
“…In addition to mediator-outcome causal relations, researchers need to carefully consider the causal structure among the mediators when multiple possible mediators are present. Two common approaches are parallel and serial mediation models (Rucker et al, 2011;Hayes, 2018): see e.g., Catapano & Tormala (2021), Jordan & Rand (2020), and Krems et al (2021) for recent use of parallel mediation models; and see e.g., Bai et al (2021), and Schumpe et al (2020) for recent use of serial mediation models.…”
Section: Mediator-mediator Causal Relationsmentioning
confidence: 99%